A note on budget balance under interim participation constraints: the case of independent types - Tilman Börgers; Peter Norman (Max Planck Institute for Research on Collective Goods, 2005)
We provide a simple proof of the equivalence between ex ante and ex post budget balance constraints in Bayesian mechanism design with independent types when participation decisions are made at the interim stage. The result is given an interpretation in terms of efficient allocation of risk.
Keywords: 330